2017
DOI: 10.15381/rivep.v28i3.13366
|View full text |Cite
|
Sign up to set email alerts
|

Expresión de los Genes de Inmunoglobulina A y Citoquinas Asociadas IL-5, IL-6 y TGF-β en Mucosa Intestinal de Crías de Alpacas (Vicugna pacos) Vacunadas con Antígeno Clostridial

Abstract: El estudio tuvo como objetivo determinar y comparar los niveles de expresión de los genes de IgA y citoquinas asociadas IL-5, IL-6 y TGF-β en la mucosa intestinal de crías de alpaca clínicamente sanas vacunadas oralmente con un antígeno clostridial. Se trabajó con 10 crías no vacunadas (control) y 15 crías vacunadas (dos dosis con intervalo de siete días). El muestreo se hizo a los siete días de la segunda dosis. Asimismo, se consideraron dos subgrupos etarios (15-28 y 35-56 días de edad en el momento de la to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…If previously answered 'as needed', how often do you need to trim their feet? (n = 88) Once a year 9.1 (8) Twice a year 15.9 (14) Three times a year 29.5 (26) More than three times a year…”
Section: Vaccinationmentioning
confidence: 99%
See 2 more Smart Citations
“…If previously answered 'as needed', how often do you need to trim their feet? (n = 88) Once a year 9.1 (8) Twice a year 15.9 (14) Three times a year 29.5 (26) More than three times a year…”
Section: Vaccinationmentioning
confidence: 99%
“…An oral vaccine for clostridial enterotoxaemia has also been investigated, with efficacy demonstrated by increased levels of immunoglobulin A in the gut of vaccinated cria. 8 However, one study showed that the effect of the injectable vaccine is short-lived and, therefore, requires frequent or strategic dosing. 6 In the past, it was advised to give a primary course, but with the decision on booster vaccinations being dependent on clostridial burden.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation